International Consultation on Incontinence 2016; Executive summary: Urodynamic testing. Issue 2 (21st December 2018) - Rosier, Peter F. W. M.; Kuo, Hann‐Chorng; De Gennaro, Mario; Gammie, Andrew; Finazzi Agro, Enrico; Kakizaki, Hidehiro; Hashim, Hashim; Toozs‐Hobson, Philip
Abstract : Aims: The International Consultation on Incontinence has published an update of the recommendations for the diagnosis and management of urine incontinence (ICI2016). This manuscript summarizes the consultations committee—recommendations with regard to urodynamic assessment. Methods: Expert consensus on the basis of structured evidence assessment has been the basis of the consultations publication and has been summarized by the committee for this manuscript. Results: Patients that are not satisfied with their initial management on the basis of their reported signs and symptoms of urinary incontinence, as well as all patients with neurological abnormalities that are potentially relevant for the function of the lower urinary tract, may very likely profit from objective diagnosis and staging and grading of their dysfunction, with urodynamic testing, regardless their age, vulnerability and/or comorbidities. The principles and technical innovations as well as the principal recommendations for the utilization of (invasive) urodynamic assessment for women, men, children, and vulnerable elderly, with or without neurogenic lower urinary tract dysfunction with urinary incontinence are provided in this abbreviated ICI recommendations‐document. Conclusions: The ICI2016 committee on urodynamics presents an executive summary of the most important reasons and recommendations for the use of urodynamic investigations for patients with urinary incontinence.